Environmental health and child survival : epidemiology, economics, experiences. (Environment and development (Washington, D.C.), 2008)
Each year, millions of children in developing countries fall sick and die from diseases caused by polluted air, contaminated water and soil, and poor hygiene behavior. Repeated infectious also contribute to malnutrition in children, and subsequently impacts future learning and productivity. This book analyzes the linkages between malnutrition and environmental health, and assesses the burden of disease on young children, and its economic costs.